An action design research on development and deployment of a computer-based group discussion support tool for achieving consensus and culture change at a tertiary educational institution - LEE, Jaclyn Mui Suan (Institutional Knowledge at Singapore Management University, 2016)
Organisational culture change is a long and complex process that typically takes years to complete and has a very low success rate. This Action Design Research Study in an educational setting, addresses the problem by the proposed use of an Action Design Research Methodology to build and deploy an IT artifact named Organisational Culture Assessment Instrument-Spilter (OCAI-Spilter) to speed up cultural change while reducing failure rate. OCAI-Spilter should be able to fast-track culture change by addressing the problem of scalability and process losses encountered in most change projects involving large numbers of people. We deploy an iterative prototyping process using Component Based Software Development to continuously refine the tool in use. We also reviewed the design principles in Action Design Research to improve the usability of the tool. New design principles and learning were derived from this process. Finally, we showed the effectiveness of the artifact by measuring the results of the tool in use through culture surveys and alignment, as well as idea generation that was administered through the tool.